2008
DOI: 10.1080/09297040701821752
|View full text |Cite
|
Sign up to set email alerts
|

Memory Functioning in Children with Reading Disabilities and/or Attention Deficit/Hyperactivity Disorder: A Clinical Investigation of their Working Memory and Long-Term Memory Functioning

Abstract: We examined memory functioning in children with reading disabilities (RD), ADHD, and RD/ ADHD using a clinic sample with a clinical instrument: the Children's Memory Scale, enhancing its generalizability. Participants included 23 children with RD, 30 with ADHD, 30 with RD/ADHD, and 30 controls. Children with RD presented with reduced verbal short-term memory (STM) but intact visual STM, central executive (CE) and long-term memory (LTM) functioning. Their deficit in STM appeared specific to tasks requiring phon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
94
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(124 citation statements)
references
References 78 publications
27
94
1
2
Order By: Relevance
“…(Table 4 about here) Discussion WM deficits have been widely studied and identified as one of the major defining characteristics of DD. Whereas the deficits in PL and CE tasks exhibited by children with DD have been reported extensively (Schuchardt et al, 2008;Smith-Spark & Fisk, 2007;Swanson et al, 2009), the findings regarding VSSP have been inconsistent (Bacon et al, 2013;Kibby & Cohen, 2008;Menghini et al, 2011). …”
Section: Predictive Effect Of Working Memory On Reading and Spelling mentioning
confidence: 76%
See 3 more Smart Citations
“…(Table 4 about here) Discussion WM deficits have been widely studied and identified as one of the major defining characteristics of DD. Whereas the deficits in PL and CE tasks exhibited by children with DD have been reported extensively (Schuchardt et al, 2008;Smith-Spark & Fisk, 2007;Swanson et al, 2009), the findings regarding VSSP have been inconsistent (Bacon et al, 2013;Kibby & Cohen, 2008;Menghini et al, 2011). …”
Section: Predictive Effect Of Working Memory On Reading and Spelling mentioning
confidence: 76%
“…Research on the relationship between DD and VSSP deficits has yielded mixed results. Although most studies have not found VSSP deficits in individuals with DD (Bacon, Parmentier, & Barr, 2013;Jeffries & Everatt, 2004;Kibby & Cohen, 2008;Schuchardt et al, 2008), others have suggested the presence of significant differences, with individuals with DD performing more poorly than TR (Menghini et al, 2011;Smith-Spark & Fisk, 2007). When visuospatial STM tasks involve CE demands, children with DD tend to exhibit more difficulties.…”
Section: Working Memory Impairments In Developmental Dyslexiamentioning
confidence: 92%
See 2 more Smart Citations
“…Another study by Kibby and Cohen (2008) provided information confirming the consistency of verbal memory deficits affecting RD and RD+ADHD groups. They applied the Children's memory scale (CMS: Cohen, 1997) to children with ADHD, RD, RD+ADHD and controls.…”
Section: Temporal Auditory Processingmentioning
confidence: 99%